Fuzzy sumudu transform / \c Norazrizal Aswad bin Abdul Rahman. - Norazrizal Aswad Abdul Rahman (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
The objectives of this research are as follows ; to propose a new integral transform in fuzzy setting, called fuzzy Sumudu transform (FST), and its fundamental results ; to construct detailed procedures for solving FDEs of integer order, FFDEs, FPDEs and SLFDEs using FST ; to analyze the results obtained for the class of FDEs considered based on the observation on graphs and tables ; to compare the results obtained using FST on the class of FDEs with the results of the class of ODEs, comprising ODEs of integer order, FrDEs, PDEs and SLDEs.